Molecular detection and genetic characterization of Resistance Genes in Shigella spp isolates Al-Diwaniyah city - Jabbar, Abeer Hamoodi; Al-Azawi, Ibtisam H (International Journal of Psychosocial Rehabilitation, 2020)
Development of antibiotics resistance in bacteria, consider as a part of evolutionary process in them has now been declared as a matter of global crisis by the World Health Organization ,It has resulted in increased failure rates of treatment of infectious diseases caused by bacteria, as drugs to which they were previously susceptible no longer works. Bacteria can be intrinsically resistant owning to its resistant mechanisms.aim of current study to detection and genetics characterization of resistance genes in Shigella spp. Shigella isolates were ) . The ereB , ereA , OXA bla , 15-M-CTX bla ( including resistance genes investigated genotypically for harboring (60%). ereB (45%) , ereA (70%) , OXA bla (60%) , 15-M-CTX bla current study recorded the highest prevalen